2019
DOI: 10.3390/ma12162517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Application of Selected Composite Materials on the Weight and Vibroactivity of the Upper Gearbox Housing

Abstract: In this paper, exploratory studies on the application of fibre-reinforced polymer composites in the construction of gearbox housing elements that are used for transport means, as an alternative to traditionally used materials, were undertaken. Composite materials with three types of reinforcement were used: a glass-chopped strand mat, glass fabric, and carbon fabric. The manufactured elements were subjected to weight assessment and vibroactivity tests, including the recording of vibration and noise. The obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…In general, damping in composites is caused by the viscoelastic behavior of the polymer matrix [41]. Although the load is transferred mainly by fibers, the matrix takes part in its transmission by means of tangential stresses [42,43,44]. In [26] the authors also showed dynamic mechanical characterization (DMA) of an unreinforced cured coupon made with the same formulation used in this paper and compared the results with those obtained with the same unfilled formulation taken as reference.…”
Section: Resultsmentioning
confidence: 99%
“…In general, damping in composites is caused by the viscoelastic behavior of the polymer matrix [41]. Although the load is transferred mainly by fibers, the matrix takes part in its transmission by means of tangential stresses [42,43,44]. In [26] the authors also showed dynamic mechanical characterization (DMA) of an unreinforced cured coupon made with the same formulation used in this paper and compared the results with those obtained with the same unfilled formulation taken as reference.…”
Section: Resultsmentioning
confidence: 99%
“…In this case, the vehicle frame needs to be strengthened at specific critical points. As often as possible, different reinforcements (profiles) are welded to the most stressed places of the frame [25].…”
Section: Carrying Steel Structurementioning
confidence: 99%
“…This has a fundamental influence on the conduction of elastic waves and their damping by multiple scattering [57]. The damping takes place mainly at high frequencies and concentrations [58,59]. The results obtained by the authors, inter alia, in their earlier works, [60] and [61], prove that FRP composites are suitable as a vibroacoustic material.…”
Section: Introductionmentioning
confidence: 99%
“…They have not been used on a large scale, but are known to be effectively applied in the gearbox housings of Formula 1 cars. Compared to cast iron or steel, FRP composites are much lighter (at least by 60% [59]). Their mechanical properties [62] are undoubtedly sufficient enough to meet the design requirements of gear housings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation